Sports Facilities and Students’ Learning Motivation: A Qualitative Study in Elementary Schools of Cimalaka District - Afghani Sya'ban Izzuddin; Entan Saptani; Anggi Setia Lengkana (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2026)
Inadequate sports facilities frequently become a major obstacle in the implementation of Physical Education, Sports, and Health (PJOK) learning at the elementary school level. This study aimed to explore the relationship between sports facilities and students’ learning motivation, as well as examine the role of teacher creativity in modifying sports equipment in elementary schools in Cimalaka District. This study employed a qualitative case study design involving three elementary schools, namely SDN Mandalaherang III, SDN Licin, and SDN Cibeureum 2. Participants consisted of three PJOK teachers, school principals, and eight students selected using purposive sampling techniques. Data were collected through in-depth interviews, observation, documentation, and student response questionnaires. The qualitative data were analyzed using thematic coding procedures assisted by NVivo software. The findings revealed three major themes: limitations of sports facilities, students’ learning motivation, and teacher strategies through equipment modification. Limited facilities reduced students’ enthusiasm and participation in physical education activities. However, teachers’ creativity in modifying sports equipment, such as sponge balls and PVC goalposts, created a safer, more engaging, and non-monotonous learning environment that enhanced students’ intrinsic motivation and active participation. The study concludes that equipment modification serves not only as a technical solution but also as a psychological intervention that supports students’ motivation despite limited school facilities.